RecruBot : Designing an HR Chatbot - Nová, Denisa; Vencovský, Filip; Krejcar, Jakub; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2020)
The aim of this bachelor thesis is to design a chatbot named RecruBot that will inform potential candidates about the company’s job opportunities. This work includes well described finalized design of the chatbot, including its structure, functionalities and components. Necessary components for chatbot construction are researched and consequently discussed. The resulting design is then evaluated based on predetermined requirements and based on conducted interview with university students of various fields of study.
Vedoucí práce: Filip Vencovský
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2020
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2020
Způsob přístupu: Internet
Keywords: aplikovaná informatika [obor bakal. práce]; bakalářské práce; bachelor's theses